Assessment of genetic diversity of Jatropha curcas L. using AFLP and ISSR markers - Sirisak Soonthornyatara (Science Faculty of Chiang Mai University, 2019)
Jatropha curcas L. (family Euphobiaceae) is widely distributed in the tropics as a potential biofuel crop. Two DNA marker techniques, AFLP and ISSR, were used to assess the genetic diversity of J. curcas germplasm collected throughout Thailand, introduced accessions from six countries and other four Jatropha species. The AFLP and ISSR fingerprint data were combined and used to evaluate genetic relationships among all samples. Pairwise similarity estimated between J. curcas ranged from 0.8428 to 1.00 with an average of 0.9955. The UPGMA cluster analysis result showed that almost all J. curcas samples were grouped into cluster 1, while a sample from USA formed separate cluster 2. The germplasms from other countries, preferably from the center of origin of this species, should be introduced to broaden genetic diversity of J. curcas in Thailand. The genetic relationship among J. curcas, J. integerrima, J. gossypifolia, J. multifida and J. podagrica was also observed. The result showed that J. integerrima was genetically more close to J. curcas than the others, while the highest value of genetic distance was found between J. curcas and J. gossypifolia. This genetic information will be useful for germplasm management in Jatropha breeding program.